CO2 emissions from reed litter in the air and on the soil surface in the Yellow River Delta, China - Tao, Baoxian; Wang, Jingdong; Jiang, Yuqing; Chen, Qinghai; Zhang, Baohua (Frontiers in Environmental Science, 2023)
The decay of litter in the air (that is, standing litter) and on the ground is an essential process of litter decomposition for many plant species. However, the contribution of standing litter to litter decomposition (e.g., CO2 emission) is still ambiguous, especially for non-leaf litter. In this study, we examined the CO2 emission from reed litter (Phragmites communis) in coastal wetlands in the Yellow River Delta (YRD), China. The results showed that the soil litter released more CO2 than the standing litter due to its rapid loss of labile organic carbon and high enzyme activities (that is, invertase and β-glucosidase). In contrast, cumulative CO2 emissions from standing litter were equivalent to 56%-70% of those on the soil surface, indicating that CO2 emissions from standing litter cannot be ignored. The sheath litter had the highest cumulative CO2 emission per unit of dry biomass among the three types of litter. Taking into account the biomass per unit area, the non-leaf litter (that is, culm and sheath) emitted more CO2 than leaf litter. On the daily scale, the litter released more CO2 at night than in the daytime, because low air temperature and high relative air humidity at night can help dew formation, accelerating CO2 emission at night. On the seasonal scale, air temperature and relative air humidity were positively related to CO2 emission, leading to rapid CO2 emission in summer and fall. The Q10 value of CO2 emission from standing litter (an average of 1.44) was lower than that of litter on the ground (an average of 2.16) due to a low residual rate of recalcitrant organic carbon in standing litter. Our findings highlight that standing litter decomposition should not be overlooked and suggest that more attention should be paid to the decay of non-leaf litter in the coastal wetland of the YRD.